The Model of Sharing Public IP Address Using Tunneling Protocol - Tomi Defisa; Thomas Budiman; Sianipar, Anton Zulkarnain (LPPM Telkom University Surabaya, 2025)
Digital Transformation cannot be separated from the support of Internet connections. The Global Internet Network only recognizes Public IP Address. The Internet Service Provider (ISP) will provide a Public IP Address to customers who subscribe to a business or Enterprise service. Companies with branch offices that subscribe to broadband internet services typically receive private IP addresses, which limits the availability of public IP addresses for systems or other purposes. This paper aims to utilize the Point-to-Point Tunneling Protocol (PPTP) and Ethernet over IP (EoIP) tunnel protocol features on MikroTik Routers for sharing a Public IP address, with a special focus on public IP Address version 4 (IPv4). Point-to-Point Tunneling Protocol (PPTP) is used to establish a Virtual Private Network (VPN) between the Head Office and Branch Office. Then, Ethernet over Internet Protocol (EoIP) is utilized to create a bridge network. Based on the test results, the Public IP Address was successfully detected on the internet network during bandwidth testing, and the route to the internet network was seen passing through the gateway from the Public IP address prefix of the Head Office. To demonstrate that Public IP Addresses can be used in Branch Offices. This model can be a solution for companies to share Public IP addresses between the head office and the Branch Office.